14,000-year Carbon Accumulation Dynamics in a Siberian Lake Reveal Catchment and Lake Productivity Changes - Hughes-Allen, Lara; Bouchard, Frédéric; Hatté, Christine; Meyer, Hanno; Pestryakova, Lyudmila A.; Diekmann, Bernhard; Subetto, Dmitry A.; Biskaborn, Boris K. (Frontiers in Earth Science, 2021)
A multi-proxy paleolimnological analysis of a sediment core sequence from Lake Malaya Chabyda in Central Yakutia (Eastern Siberia, Russia) was conducted to investigate changes in lake processes, including lake development, sediment and organic carbon accumulation, and changes in primary productivity, within the context of Late Pleistocene and Holocene climate change. Age-depth modeling with 14C indicates that the maximum age of the sediment core is ~14 cal kBP. Three distinct sedimentary units were identified within the sediment core. Sedimentological and biogeochemical properties in the deepest section of the core (663–584 cm; 14.1–12.3 cal kBP) suggests a lake environment mostly influenced by terrestrial vegetation, where organic carbon accumulation might have been relatively low (average ~ 100 g OC m-2 a-1), although much higher than the global modern average. The middle section of the core (584–376 cm; 12.3–9.0 cal kBP) is characterized by higher primary productivity in the lake, much higher sedimentation, and a remarkable increase in OC delivery (average ~300 g OC m-2 a-1). Conditions in the upper section of the core (< 376 cm; < 9.0 cal kBP) suggest high primary productivity in the lake and high OC accumulation rates (average ~ 200 g OC m-2 a-1), with stable environmental conditions. The transition from organic-poor and mostly terrestrial vegetation inputs (TOC/TNatomic ratios ~ 20) to conditions dominated by aquatic primary productivity (TOC/TNatomic ratios < 15) occurs at around 12.3 cal kBP. This resulted in an increase in the sedimentation rate of OC within the lake, illustrated by higher sedimentation rates and very high total OC concentrations (> 30%) measured in the upper section of the core. Compact lake morphology and high sedimentation rates likely resulted in this lake acting as a significant OC sink since the Pleistocene-Holocene transition. Sediment accumulation rates declined after ~8,000 cal k BP, however total OC concentrations were still notably high. TOC/TNatomic and isotopic data (13C) confirm the transition from terrestrial-influenced to aquatic-dominated conditions during the Early Holocene. Since the mid-Holocene, there was likely higher photosynthetic uptake of CO2 by algae, as suggested by heavier (isotopically enriched) 13C values (> -25 ‰).